THE INFLUENCE OF INTERNAL ENVIRONMENT AND SELF-EFFICACY ON EMPLOYEES’ WORK MOTIVATION AT PT. DAKA GROUP - Nehru Putri, Triwulandari; Windayani; Azis Muthalib, Dzulfikri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyze the influence of the internal environment and self-efficacy on employees’ work motivation at PT. Daka Group. The research employed a quantitative approach using a census sampling method, involving all 60 permanent employees of PT. Daka Group as respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that the internal environment and self-efficacy simultaneously have a positive and significant effect on employees’ work motivation. Partially, both the internal environment and self-efficacy also show a positive and significant impact on work motivation. These findings confirm that a supportive internal environment fosters comfort, harmonious relationships, and effective communication, which enhance motivation. Additionally, employees with high self-efficacy tend to be more confident in handling tasks and overcoming work challenges, leading to higher motivation. It is recommended that PT. Daka Group continually improve the quality of its internal work environment and implement development programs to strengthen employees’ self-efficacy as strategic efforts to maintain and enhance work motivation.